2017
DOI: 10.1111/lsq.12165
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Principals and Legislative Cohesion

Abstract: In many systems, legislators find themselves accountable to multiple principals. This article seeks to further answer how legislators decide between their principals and what factors condition legislators to choose one over the other. We argue that electoral uncertainty, operationalized as electoral volatility, pushes legislators towards the principal that has the greatest influence over their re-election. Using European Parliament electoral results and roll-call data from the second to the sixth European Parl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 76 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…Meserve et al. () show that electoral volatility in EP elections – at member state level, between 1984 and 2009 – increased MEPs’ attention to the domestic arena, strengthened the dominance of the national party principal and, accordingly, drove up individual defection.…”
Section: When Politics Trumps Loyalty: An Explanatory Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Meserve et al. () show that electoral volatility in EP elections – at member state level, between 1984 and 2009 – increased MEPs’ attention to the domestic arena, strengthened the dominance of the national party principal and, accordingly, drove up individual defection.…”
Section: When Politics Trumps Loyalty: An Explanatory Frameworkmentioning
confidence: 99%
“…: 39; 41–47; Meserve et al. : 10). National media rarely scrutinise EU lawmaking, but the defection of a delegation from its domestic base makes ‘headlines’ – especially before an election (Lindstädt et al.…”
Section: When Politics Trumps Loyalty: An Explanatory Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, voting dissent is most likely to occur when there is a divergence in the preferences of the two principals of the MEP: the EPG and the national party (Hix, ). Thus, it is not surprising that previous studies (Faas, ; Hix, , ; Lindstädt et al, ; Meserve et al ., ) have shown that policy conflict between the national party and the EPG is a major predictor of MEP defection at roll‐call votes. These studies have measured policy conflict using the distances between the two principals of the MEP on the left–right scale and on the EU integration dimension.…”
Section: Theoretical Frameworkmentioning
confidence: 99%